Demystifying the Labyrynth of The Delta: An Ecolinguistic Appraisal of Selected Poems of Tanure Ojaide - Zakariyah, Moshood; Olugbodi, Mariam (Universitas Negeri Padang, 2023)
AbstractEcological issues in the context of Niger-Delta, Nigeria have been approached mostly from the perspective of environmental degradation, and marginalisation in previous studies. However, in literary pieces, which are mostly the dominant objects of analysis in those studies, there are underlying linguistic imports, which are reflexive of the beauty of the literary discourses revolving around the Niger-Delta environment. It is based on this backdrop that this study sets out to examine selected poems of Tanure Ojaide from an ecolinguistic perspective. To achieve the aim of the study, five poems are selected purposively from Ojaide’s Songs of Myself and analysed using both qualitative and quantitative approaches to data analysis. The data is also examined using the Eco-critical Discourse Analysis (EDA) approach. The findings from the study reveal the use of rhetorical devices to converge towards emphasising the beauty of the ecological characteristics of the physical environment. The use of imagery by the poet draws on readers’ socio-cognitive instincts towards the appealing to their emotive senses. In conclusion, the use of the eco-linguistic approach to examine the poems has not only revealed the poet’s intents but has also demystified the myth behind the ecosystem of the Niger Delta.